The Influence of Augmented Reality (AR) Learning Media with Assemblr Studio on Students’ Technological Literacy - Mulia Nissa; Diana Hernawati; Samuel Agus Triyanto (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2026)
Technological literacy is one of the essential competencies of the 21st century; however, the level of technological literacy among students at MAN 2 Kota Tasikmalaya remains relatively low. This condition underscores the need for innovative learning approaches grounded in digital technology. This study aims to analyze the effect of Augmented Reality (AR) learning media using Assemblr Studio on students’ technological literacy in biology subjects. The research employed a quasi-experimental, post-test-only, non-equivalent-group design. The sample consisted of two classes: class XI 4 as the experimental group (using AR media) and class XI 1 as the control group (using PowerPoint), selected through purposive sampling. Data were collected using a technological literacy questionnaire with a Likert scale comprising 20 statements across four indicators: content, process, context, and attitude. The results of the Independent Samples T-Test showed a significant value of 0.000 (<0.05), indicating a significant effect. Additionally, the effect size (Cohen’s d) was 1.14, which falls into the high category. Therefore, AR-based learning media developed with Assemblr Studio proved effective in enhancing technological literacy through interactive, visual, and engaging learning experiences.